Tantangan dan Perkembangan Vaksin HIV (Human Immunodeficiency Virus) - Wil hel minah; Rahma Ziska; Mohamad Isronijaya (Syntax Corporation Indonesia, 2022)
Antiretroviral therapy (ART) is the first treatment for HIV/AIDS cases, it is known to improve the patient's quality of life, but cannot cure HIV infection. HIV is a virus that infects CD4+, this infection can cause cell death. Vaccines are an effort that can prevent infection, but until now an HIV vaccine has not been found, this systematic review was conducted to find out the challenges and developments of HIV vaccines to date, the challenge of developing an HIV vaccine is the ability to induce Broadly Neutralizing Antibodies (bNAbs). The protein subunit vaccine platform developed an Env trimeric mock design to be able to expose the bNAbs epitope, but from various designs it has not been proven successful, trimeric design methods and stabilization and purification strategies greatly affect the quality of Env protein. New strategies have emerged with more modern methods, mRNAs for enhancing expression and self-amplifying alphavirus-derived ones have shown potential in a preclinical assay of the GT-based 60mer eOD-GT8 vaccine to promote GC response and elicit somatic hypermutation, resulting in the VRC01 class bnAbs which are antibodies that most widely used for HIV-1 vaccine efficacy. In addition, targeting dendritic cells with mRNA transfection as a therapeutic therapy offers HIV-specific T cell responses, until now research on dendritic cell vaccines in HIV-1-infected patients is still in the process of optimizing for a stronger and longer-lasting immune response, establishing a control period. the length of viral replication along with eliminating the viral reservoir and factors preventing viral re-emergence, two of which are influential, namely the general condition of the patient (genetic factors and clinical status) and the vaccine product.